Effect of Follicular Substances on Phytochemical Profile and Antioxidant Capacity of Ketip Banana (Musa paradisiaca Forma typiaca) Peel Ethanol Extract - Bahri, Syamsul; Hijriani, Baiq Isti; Wirdullutfi, Wirdullutfi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
A healthy lifestyles require both synthetic antioxidants and those sourced from food. Antioxidants can be obtained from food ingredients or can also be synthetic oxidants. Antioxidants derived from plants contain quite high levels. One type of tropical fruit contains antioxidants is the banana, and one cultivar of banana is Musa paradisiaca Forma typiaca, locally name is Ketip. The research aimed to compare the phytochemical profile of peel ethanol extract of this cultivar using different sample preparation techniques and then compare the antioxidant capacity of the extracts using the DPPH method. This research employed two types of techniques in preparing the sample. The first one leaves the sap attached to the sample, the second one uses tissue paper to reduce the follicular substances, soon after chopping the sample. Phytochemical results of the extract prepared by the first technique showed that the extract contains flavonoids, alkaloids, saponins, terpenoids, and tannins, while the extract prepared by the second technique also detected phenolic compounds. Despite the phytochemical profile showing no difference at all from both techniques, their antioxidant capacity showed a significant difference. The IC50 score of the extract prepared by the first technique was 554,84. This score is categorized in the very weak activity group, whereas the IC50 score of the extract prepared by the second technique was 202,13. This score is categorized in the intermediate activity group. It is concluded that the follicular substances significantly increase the IC50 score of ethanol extract of Ketip banana peel.